THE EFFECT OF E-CALF ON THE FIFTH GRADE STUDENTS’ READING COMPREHENSION AT SD LAB UNDIKSHA - K.D. Septiyaningsih; N.W.S. Mahayanti; G.A.P. Suprianti (Language and Education Journal Undiksha, 2019)
e-CALF is an acronym for Electronic-Contextual, Attractive, Logic, and Fun - an electronic game developed as a learning medium to facilitate students' reading comprehension. This study aims to determine the effect of e-CALF on the reading comprehension of grade 5 elementary school students at SD Undiksha Lab. This study applies a post-test only control group as a design. The population of this study was the 5th grade students of Undiksha Elementary School. Selected 12 students from class 5A as an experimental group and 12 people from class 5B as a control group. Data were collected using a post-test instrument in the form of multiple choice. From the results of the SPSS analysis, the results showed that the average reading comprehension of the experimental group students was higher than the average reading comprehension of the control group students.